1991
DOI: 10.1111/1540-5885.830170
|View full text |Cite
|
Sign up to set email alerts
|

When Technologies Compete: The Role of Externalities in Nonlinear Market Response

Abstract: When competing technologies are introduced at about the same time, they may either share the market for an extended period or one may eventually dominate the other. Using actual data from the VCR market, William Redmond explores product and market conditions that favor the emergence of a dominant technology. Recent developments in the theory of nonlinear economic processes yield straightforward models of the dominant or all‐or‐nothing response pattern. In this study, the role of externalities, or infrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…A larger user population means that there are more opportunities to share information, support, and content with others (Watanabe and Hobo 2004). Prior research has also found that when consumers know that network externalities exist, they are more likely to influence their friends and relatives to adopt the product (Redmond 1991) than when network externalities are absent.…”
Section: Moderating Effectsmentioning
confidence: 99%
“…A larger user population means that there are more opportunities to share information, support, and content with others (Watanabe and Hobo 2004). Prior research has also found that when consumers know that network externalities exist, they are more likely to influence their friends and relatives to adopt the product (Redmond 1991) than when network externalities are absent.…”
Section: Moderating Effectsmentioning
confidence: 99%
“…Therefore, it is natural to assess the gains from this complexity by benchmarking our approach against simpler and less-demanding models that can also address network externality effects. We compare our model against two benchmark models: the analogical diffusion model of Bayus (1993) and the Positive Feedback Market Share Model proposed by Redmond (1991). The Bayus Model: Bayus (1993) uses historical data on sales and prices of 27 consumer durables to develop a product segmentation scheme based on demand parameters as well as marketing and manufacturing related variables.…”
Section: Benchmarking Validation and Robustness To Assumptionsmentioning
confidence: 99%
“…Vários estudos Perugini & Bagozzi, 2001;Fekadu & Kraft, 2001) já comprovaram a influência das pressões normativas sob a intenção de compra e que tal relação é ainda mais forte quando se refere a aspectos ligados à aceitação e uso de produtos ou serviços com inovações (Shurmer, 1993;Westland, 1992;Redmond, 1991;Shankar & Bayus, 2004 Davis (1989). Seu objetivo inicial era o de apresentar um instrumento para prever a probabilidade de uma nova tecnologia ser adotada dentro de um grupo ou uma organização.…”
Section: Modelos De Aceitação De Inovações Tecnológicas (Tam E Tra)unclassified